Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Express a complex number in modulus amplitude form

$\displaystyle 1+\sin \alpha +i\cos \alpha $

My Attempt:

$\displaystyle r\cos \theta= 1+\sin \alpha $

$\displaystyle r\sin \theta= \cos \alpha $

Squaring and adding.. $\displaystyle r^2= (1+\sin \alpha)^2+ \cos^2 \alpha$

$\displaystyle r^2= 2(1+\sin \alpha) $

$\displaystyle \tan \theta = \frac{\cos \alpha}{1+\sin \alpha} $

How to break up $\displaystyle 1+\sin \alpha $?

share|improve this question

3 Answers 3

up vote 2 down vote accepted

It is better to solve it this way:

$$\begin{aligned} 1+\sin\alpha+i\cos \alpha &=1+\cos\left(\frac{\pi}{2}-\alpha\right)+i\sin\left(\frac{\pi}{2}-\alpha\right)\\ & \stackrel{*}{=}2\cos^2\left(\frac{\pi}{4}-\frac{\alpha}{2}\right)+i2\sin\left(\frac{\pi}{4}-\frac{\alpha}{2}\right)\cos\left(\frac{\pi}{4}-\frac{\alpha}{2}\right)\\ &=2\cos\left(\frac{\pi}{4}-\frac{\alpha}{2}\right)\left(\cos\left(\frac{\pi}{4}-\frac{\alpha}{2}\right)+i\sin\left(\frac{\pi}{4}-\frac{\alpha}{2}\right)\right)\\ &=2\cos\left(\frac{\pi}{4}-\frac{\alpha}{2}\right)e^{i\left(\pi/4-\alpha/2\right)}\\ \end{aligned}$$

$(*)$, In this step I used the following formulas:

$\cos(2x)=2\cos^2x-1$ and $\sin(2x)=2\sin x\cos x$


In your method, I am not seeing how you get that expression for $\tan\theta$. Rather it should be $\tan\theta=\dfrac{\cos\alpha}{1+\sin\alpha}$. Hence,

$$\tan\theta=\frac{\sin\left(\frac{\pi}{2}-\alpha\right)}{1+\cos\left(\frac{\pi}{2}-\alpha\right)}=\frac{2\sin\left(\frac{\pi}{4}-\frac{\alpha}{2}\right)\cos\left(\frac{\pi}{4}-\frac{\alpha}{2}\right)}{2\cos^2\left(\frac{\pi}{4}-\frac{\alpha}{2}\right)}$$ $$\Rightarrow \tan\theta=\tan\left(\frac{\pi}{4}-\frac{\alpha}{2}\right)$$

share|improve this answer

Hint

Another way would consist in writing $$\displaystyle 1+\sin( \alpha) +i\cos( \alpha)=\Big(\sin(\frac{\pi}{2})+\sin( \alpha)\Big)+i \Big( \cos(\frac{\pi}{2})+\cos( \alpha)\Big)$$ Now, apply $$\sin(p)+\sin(q)=2 \sin \left(\frac{p+q}{2}\right) \cos \left(\frac{p-q}{2}\right)$$ $$\cos(p)+\cos(q)=2 \cos \left(\frac{p+q}{2}\right) \cos \left(\frac{p-q}{2}\right)$$

I am sure that you can take from here.

share|improve this answer

A general fact is: $$\forall z\in\mathbb{C},\ \lvert z\rvert^2+z^2=z(\overline z+z)=2\Re(z)z.$$ (a manifestation of the inscribed angle theorem?). Hence: $$\forall z\in\mathbb{C},\ \bigl\lvert\lvert z\rvert^2+z^2\bigr\rvert=2\bigl\lvert\Re(z)\bigr\rvert\lvert z\rvert,\ \text{and}\ \arg(z)=\begin{cases}\arg(z)&\text{if $\Re(z)>0$}\\\arg(z)+\pi&\text{if $\Re(z)<0$}\end{cases}$$ In your case, setting: $$z=\mathrm{e}^{i(-\alpha/2+\pi/4)}$$ yields $$z^2=\mathrm{e}^{i(-\alpha+\pi/2)}=i\mathrm{e}^{-i\alpha}=i(\cos\alpha-i\sin\alpha)=\sin\alpha+i\cos\alpha$$ and $$\lvert z\rvert=1.$$ We also have $$\Re(z)=\cos(-\alpha/2+\pi/4).$$ Hence $$1+\sin\alpha+i\cos\alpha=\begin{cases}2\cos(-\alpha/2+\pi/4)\mathrm{e}^{i(-\alpha/2+\pi/4)}&\text{if $\cos(-\alpha/2+\pi/4)\geq0$}\\-2\cos(-\alpha/2+\pi/4)\mathrm{e}^{i(-\alpha/2-3\pi/4)}&\text{if $\cos(-\alpha/2+\pi/4)\leq0$.}\end{cases}$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.